Epilepsy and recommendations for breastfeeding. (May 2015) - Veiby, Gyri; Bjørk, Marte; Engelsen, Bernt A.; Gilhus, Nils Erik
Highlights: Breastmilk is the optimal source of nutrition for infants. Most AEDs are safe or moderately safe during breastfeeding, and side effects in breastfed neonates are rare. Prospective studies show no adverse developmental effects of AED exposure via breastmilk. Women taking AEDs should be encouraged to breastfeed. Surveillance of side effects and measures to minimize the infant's drug dose should be undertaken. Abstract: Purpose: The objective of this paper is to provide a synopsis of benefits and potential harmful effects of exposure to antiepileptic drugs (AEDs) via breastmilk, and present recommendations for breastfeeding in women with epilepsy. Methods: The article is based on a discretionary selection of English language articles retrieved by a literature search in the PubMed database, the LactMed database, and the authors' clinical experience. Results: Breastfeeding is associated with benefits for the infant, including nutrition, protection against infectious and immunological disease, and promotion of development and psychological attachment. Exposure to AEDs via breastmilk could potentially produce side effects or negatively affect development. Most studies on AED transfer through breastmilk report infant serum levels well below the limit of an expected pharmacological effect. Some drugs have the potential to reach significant serum levels in breastfed infants, such as barbiturates, benzodiazepines, lamotrigine, and ethosuximide. Thus, breastfed infants should be monitored for side effects. Still, adverse symptoms are rarely reported in breastfed infants of mothers taking AEDs, and prospective studies have failed to demonstrate any negative developmental effects in children that have been exposed to AEDs via breastmilk. The nursing infant's degree of drug exposure can be minimized by breastfeeding when drug concentrations in the milk are low, reducing maternal AED dosage to prepregnancy levels, and administering mixed nutrition. Conclusion: Most AEDs are considered safe or moderately safe during breastfeeding. Mothers with epilepsy should be encouraged to breastfeed, provided careful monitoring of the infant.